Analisa Hasil Pengelasan Antara Trafo Las Kumparan Lilitan Pabrikan Dengan Konvensional - Usman; Cahyadi, Catra Indra; Paino; Hasibuan, Eriansyah S (Jurnal Mahajana Informasi, 2024)
The electric welding system requires a welding transformer that is usually classified as direct current (DC) or alternating current (AC). In electric welding, a separate transformer is provided as a source for regulating the required current during the welding process. The operation of the transformer during welding is closely related to the needs of the current, the diameter of the welding wire, and the thickness of the material being welded. The difference between a conventional coil winding transformer and a manufacturer's coil winding transformer lies in the welding results and the specimens obtained from testing a type of material, which is steel plate ST37 with a thickness of 8mm and a width of 40mm, using electrodes E-6013 with diameters of 2.6mm and 3.2mm. The welding joint method used is a single V groove butt joint. The welding tests of both transformers prove that the penetration, width, and height of the weld bead with the Manufacturer's coil winding transformer are quite good compared to the Conventional coil winding transformer. Based on the welding test results of both transformers, the Manufacturer's coil winding transformer using electrode type E-6013 achieved the highest bending test strength with a Crack load value of 33.701 kN, while the Conventional coil winding transformer had a value of 27.335 kN, both using the same current of 120 Amperes.".